Communication as Physical Health Therapy - Imam Khalid; Oktri Permata Lani (Alfuad: Jurnal Sosial Keagamaan, 2024)
Communication is a means of providing stimulus to the communicant in changing a person's behavior and feelings, especially in the relationship between paramedics and patients. Interpersonal communication in the world of health is known as therapeutic communication, communicating with patients is to help, assist and lighten the burden of illness suffered by the patient. This article discusses communication as a means of providing encouragement and support to patients in the healing process, as well as the principles and techniques that paramedics must use with patients. Based on data collected and analyzed entirely from literature and other documentation materials, such as writings in journals and other relevant media, this article argues that interpersonal communication can be used as therapeutic communication to patients. The essence of interpersonal relationships in therapeutic communication is warmth, sincerity, empathetic understanding and positive attention. As a communicator, you are able to show attention, through messages through soft, ethical speech to patients, so that you can help patients in the healing process